Analisis Kepuasan Pengguna Trans Metro Deli Dengan Metode Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) (Studi Kasus: Koridor 5 Tembung – Lapangan Merdeka) - Pangaribuan, Lia Agistin Br; Wirawan, I Gede; Pangaribuan, Martha Olivia Pama; Hidayat, Dwi Wahyu (FSTPT Indonesia, 2024)
Medan, as the capital city of North Sumatra Province, plays a significant role in the social, cultural, and tourism sectors. Rapid economic growth in this city has resulted in traffic congestion and an inadequate transportation system. The government's introduction of Trans Metro Deli, a Bus Rapid Transit (BRT) service, aims to improve the quality of transportation and reduce congestion. This study was conducted in 2023 using qualitative and quantitative data. Questionnaires were distributed to 100 respondents using Trans Metro Deli buses in the Tembung-Lapangan Merdeka corridor. The data obtained were analyzed using the CSI and IPA methods. The research findings show that the satisfaction level of Trans Metro Deli users reaches 80.19%, which falls into the